Excessive Cry in a 5-Month-Old Infant Possibly due to Abdominal Epilepsy - Roy, Soumya; Majumdar, Sumit Datta; Chakrabartty, Subroto; Chakravarti, Swati (Journal of Pediatric Epilepsy, 2017)
Excessive and unexplained cry is a common problem with infants. Most of the causes are benign or easily treatable, with exception of a few. However, we encountered a 5-month-old, otherwise healthy male infant, who used to cry inconsolably every day on the afternoon for about 3 hours and then used to fall asleep. This had been going on for the last 6 weeks. After waking up, infant seemed perfectly normal. History, physical examination, and routine investigations failed to diagnose the cause. An electroencephalogram showed epileptic abnormalities. The “crying episodes” disappeared after starting phenobarbitone. Although two of the four criteria for diagnosis of abdominal epilepsy (AE) are impossible to be met in an infant of this age (because he cannot speak out his ailments whether he is having abdominal pain, headache, dizziness, etc.); still we believe that this was a case of AE. Various case reports have stated that “sustained response to anticonvulsants has been accepted as one of the criteria for the diagnosis of AE.” We suggest AE to be kept in mind even when dealing with an infant of unresolved excessive crying.
Keywords: infant; abdominal epilepsy; excessive cry